A new equation to estimate temperature-corrected PaCO2 from PETCO2 during exercise in normoxia and hypoxia - Gonzalez Henriquez, J. J.; Losa-Reyna, J.; Torres-Peralta, R.; Rådegran, G.; Koskolou, M.; Calbet, J. A. L. (Scandinavian Journal of Medicine & Science in Sports, 2016)
End-tidal PCO2 (PETCO2) has been used to estimate arterial pressure CO2 (PaCO2). However, the influence of blood temperature on the PaCO2 has not been taken into account. Moreover, there is no equation validated to predict PaCO2 during exercise in severe acute hypoxia. To develop a new equation to predict temperature-corrected PaCO2 values during exercise in normoxia and severe acute hypoxia, 11 volunteers (21.2 ± 2.1 years) performed incremental exercise to exhaustion in normoxia (Nox, PIO2: 143 mmHg) and hypoxia (Hyp, PIO2: 73 mmHg), while arterial blood gases and temperature (ABT) were simultaneously measured together with end-tidal PCO2 (PETCO2). The Jones et al. equation tended to underestimate the temperature corrected (tc) PaCO2 during exercise in hypoxia, with greater deviation the lower the PaCO2tc (r = 0.39, P < 0.05). The new equation has been developed using a random-effects regression analysis model, which allows predicting PaCO2tc both in normoxia and hypoxia: PaCO2tc = 8.607 + 0.716 × PETCO2 [R2 = 0.91; intercept SE = 1.022 (P < 0.001) and slope SE = 0.027 (P < 0.001)]. This equation may prove useful in noninvasive studies of brain hemodynamics, where an accurate estimation of PaCO2 is needed to calculate the end-tidal-to-arterial PCO2 difference, which can be used as an index of pulmonary gas exchange efficiency.